Energy and exergy analyses of single and double reheat irreversible Rankine cycle - Gonca, Guven (INDERSCIENCE ENTERPRISES LTD, 2015)
In this paper, energy and exergy analyses based on the thermal efficiency, exergy efficiency, exergetic performance criterion, exergy destruction and net specific work output have been performed for irreversible single reheat Rankine cycle (SRRC) and double reheat Rankine cycle (DRRC). The effects of the reheat pressure, boiler pressure and boiler temperature on the general and optimal performance of the cycle are investigated by taking into account the mechanical, boiler and isentropic efficiencies. The maximum values of the exergy efficiencies and specific net work outputs and their corresponding reheat pressures are obtained for the SRRC and DRRC. It is pointed out that exergy efficiencies and specific net work outputs are considerably affected by the reheat pressure, the boiler pressure and the boiler temperature for both of the cycles.
Keywords: exergy efficiency; thermal efficiency; net work output; Rankine cycle; performance analysis; exergetic performance coefficient; GEOTHERMAL POWER-PLANT; THERMODYNAMIC ANALYSIS; NUMERICAL OPTIMIZATION; TRIGENERATION SYSTEM; HEATING-SYSTEM; COGENERATION; ENGINE; EFFICIENCY; REDUCTION; Thermodynamics; Energy & Fuels